1999
DOI: 10.3346/jkms.1999.14.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in child psychiatric patients

Abstract: To determine the frequency of chromosomal abnormalities in a child psychiatric population, and to evaluate possible associations between types of abnormalities and patient's clinical characteristics, cytogenetic examination was performed on 604 patients. Demographic data, reasons for karyotyping, clinical signs, and other patient characteristics were assessed and correlated with the results from karyotyping. Chromosomal abnormalities were found in 69 patients (11.3%); these were structural in 49 cases and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thirteen articles on FXS published in Korea since 1993 were reviewed ( 6 - 18 ) and its summary is presented in Table 2 . The positive rate of FXS was in the range of 0.77-8.51%, depending on the study groups and the method of diagnosis ( 6 , 8 , 9 , 11 , 13 - 15 , 17 ) The prevalence survey for 699 neonates showed 0.43% of premutation of FMR1 ( 16 ). There was a case report of prenatal diagnosis for the fetus from the mother of known premutation of FMR1 , which showed that the fetus had full mutation of FMR1 ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles on FXS published in Korea since 1993 were reviewed ( 6 - 18 ) and its summary is presented in Table 2 . The positive rate of FXS was in the range of 0.77-8.51%, depending on the study groups and the method of diagnosis ( 6 , 8 , 9 , 11 , 13 - 15 , 17 ) The prevalence survey for 699 neonates showed 0.43% of premutation of FMR1 ( 16 ). There was a case report of prenatal diagnosis for the fetus from the mother of known premutation of FMR1 , which showed that the fetus had full mutation of FMR1 ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Contribution of chromosome aberrations to DD/MR is generally said to be elevated. Chromosome abnormalities are reported in 4–34.1% of individuals with DD/MR [Bourgeois and Benezech, 1977; Kodama, 1982; Opitz et al, 1982; Rasmussen et al, 1982; Wuu et al, 1984; Gustavson, 1977b; Srsen et al, 1989; Wuu et al, 1991; Phelan et al, 1996; Felix et al, 1998; Hou et al, 1998; Battaglia et al, 1999; Hong et al, 1999; Cora et al, 2000], and cytogenetic analysis is regarded as a mainstay in the diagnostic process. However, guidelines regarding the type and resolution of the analysis to be performed and definite clinical indications for such studies are still debated.…”
Section: Cytogenetics/molecular Cytogeneticsmentioning
confidence: 99%
“…Cytogenetic studies conducted by Shin on 259 children with LD, Hong, on 604 children, also proved the significance and effects of karyotyping in identifying chromosomal abnormalities. 15,16 Out of the 86 children studied cytogenetically, two showed chromosome deletions involving chromosomes 4 and chromosome 20, 2 showed translocations between chromosomes 3 and 12 and also between chromosomes 13 and 14 and another 2 showed ring chromosomes, involving chromosomes 1 0 and 15.…”
Section: Resultsmentioning
confidence: 99%